СОЦИАЛ ПСИХОЛОГИК КОМПЕТЕНТЛИККА ТАЪСИР ЭТУВЧИ ОМИЛЛАР - ganjiyev, feruz (Центр Научных Публикаций (buxdu.uz), 2022)
The article discusses the methodology of formation of the general (basic) competence of pedagogical personnel,including preschool teachers,its basic structure.